Reducing Academic Stress with Journaling Techniques: A Review - Siregar, Ilham Khairi; Sari, Ifit Novita (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2021)
The education process in higher education allows new students to feel the pressure of changing the learning process from high school to the lecture process in higher education. Students with considerable pressure feel the academic stress condition in themselves. Academic resilience is expected to reduce student academic stress, namely increasing student resilience in facing difficulties and pressures in the lecture process. Journaling technique is an alternative treatment that can be given to students, as part of the rational emotive behavior therapy approach. This figure suggests an expressive writing technique to cognitive gaps (academic stress) experienced by students.